Pelaksanaan program pelatihan Parenting Skills pada kelompok ibu rumah tangga di Desa Tanabangka Kecamatan Bajeng Barat Kabupaten Gowa - Ahmad Razak (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This activity aims to: 1) increase parenting knowledge that is appropriate to the child's development in the group of housewife. 2) forming parenting skills in the group of housewife. Participants were a group of 30 housewife who were selected by purposive sampling. The results of this activity 1) increased good knowledge about parenting that is appropriate for children's development. 2) formed parenting skills in the group of housewife